Cardiopulmonary resuscitation knowledge and skills of registered nurses in Botswana - Lakshmi Rajeswaran; Valerie J. Ehlers (AOSIS, 2014)
Background: In Botswana nurses provide most health care in the primary, secondary and tertiary level clinics and hospitals. Trauma and medical emergencies are on the increase, and nurses should have cardiopulmonary resuscitation (CPR) knowledge and skills in order to be able to implement effective interventions in cardiac arrest situations. Objective: The objective of this descriptive study was to assess registered nurses' CPR knowledge and skills. Method: A pre-test, intervention and re-test time-series research design was adopted, and data were collected from 102 nurses from the 2 referral hospitals in Botswana. A multiple choice questionnaire and checklist were used to collect data. Results: All nurses failed the pre-test. Their knowledge and skills improved after training, but deteriorated over the three months until the post-test was conducted. Conclusion: The significantly low levels of registered nurses' CPR skills in Botswana should be addressed by instituting country-wide CPR training and regular refresher courses.